1992
DOI: 10.1128/jb.174.23.7717.1992
|View full text |Cite
|
Sign up to set email alerts
|

FtsL, an Essential Cytoplasmic Membrane Protein Involved in Cell Division in Escherichia coli

Abstract: We have identified a gene involved in bacterial cell division, located immediately upstream of the ftsI gene in the min 2 region of the Escherichia coli chromosome. This gene, which we named ftsL , was detected through characterization of Tn phoA insertions in a plasmid containing this chromosomal region. Tn phoA topological analysis and fractionation of alkaline phosphatase fusion proteins i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
150
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(155 citation statements)
references
References 45 publications
5
150
0
Order By: Relevance
“…N-terminal sequencing yielded the sequence VKEYDIVA. Combining the mass and sequence data indicated that the fragment spans residues 220 to 361 of pneumococcal DivIB (15,843 Da). This fragment overlaps the ␤-domain defined by the structure of FtsQ from E. coli, and is somewhat longer on the C-terminal side than the ␤-domain defined by partial proteolysis of DivIB from G. stearothermophilus.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…N-terminal sequencing yielded the sequence VKEYDIVA. Combining the mass and sequence data indicated that the fragment spans residues 220 to 361 of pneumococcal DivIB (15,843 Da). This fragment overlaps the ␤-domain defined by the structure of FtsQ from E. coli, and is somewhat longer on the C-terminal side than the ␤-domain defined by partial proteolysis of DivIB from G. stearothermophilus.…”
Section: Resultsmentioning
confidence: 99%
“…Both ␤ and ␤␥ contain an additional N-terminal glycine resulting from cleavage of the fusion with the GST using the TEV protease. 15 N atoms, i.e. the amide protons of the backbone chain and the few amine protons from side chains.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells were grown routinely in NZY medium (15). For testing growth on minimal medium M63 was used as described (14).…”
Section: Methodsmentioning
confidence: 99%